Enhanced mechanical, tribological and corrosion properties of graphite and carbon nanotube-reinforced copper-based hybrid composites - Kara, Gamze Ispirlioglu; Sezek, Sinan; Aksakal, Bunyamin (Sage Publications Ltd, 2024)
Copper (Cu)-based hybrid composites were fabricated by powder metallurgy, incorporating Graphite (Gr) and Carbon nanotube (CNT) reinforcements at various fractions. The composites were formed using a cold pressing technique and subsequently sintered at various temperatures. The structural properties of the hybrid composites were evaluated using Scanning Electron Microscopy (SEM), Energy Dispersion Spectrum (EDX) and X-ray diffraction (XRD). Hardness, compression, wear and corrosion tests were performed to show the effect of the reinforcements. It was shown that the hardness of Gr and CNT reinforcements have significantly improved the properties of pure Cu. The Cu-Gr-2CNT hybrid composite, which was subjected to sintering at a temperature of 850 degrees C, exhibited the highest level of hardness, showing a significant increase of 51.4% in comparison to the pure Cu sample. While the compressive stresses increased in the Cu matrix with the addition of Cu-Gr, it increased to 350 MPa with the addition of 2 wt% CNT. The hardness value exhibited a similar increase and was measured to be 122 HV in Cu-Gr-2CNT. During the wear tests, the coefficient of friction values fell by 9.2% for Cu-2CNT, by 3.88% for Cu-CNT, by 3.92% for Cu-Gr-2CNT, and by 5.27% for Cu-Gr-CNT, as compared to pure Cu. The comprehensive findings demonstrated that the tests and analyses yielded consistent results, and the utilization of various combinations of Gr and CNT reinforcements enhanced the mechanical, tribological, and corrosion resistance properties of the fabricated hybrid composites. Nevertheless, the combination of Cu-Gr-2CNT yielded the most advantageous outcomes.
Keywords: Hybrid composites; copper; graphite; carbon nanotube; tribology; corrosion